CSR and Leadership Approaches and Practices: A Comparative Inquiry of Owners and Professional Executives. Issue 4 (20th August 2018) - Yamak, Sibel; Ergur, Ali; Karatas‐Ozkan, Mine; Tatli, Ahu
Abstract : This study generates comparative insights into CSR approaches of owners and non‐kin professional executives in an emerging country context, Turkey. Drawing on 61 interviews, we found that ownership status of the executive is crucial in shaping their CSR perceptions and practices. Owner‐executives are empowered in pursuing CSR approaches based on their personal preferences and values; they have mostly societal aims. Professionals display tendency for company‐related CSR practice; they exhibit greater knowledge of CSR, and their CSR initiatives are the results of strategic choices to enhance their power within the corporation. Our paper contributes to the debate on the drivers for CSR by accounting for both societal and individual influences on the CSR agency of these two key groups of executives. First, we develop a typology of CSR approaches of owners and professionals. Second, we provide insights from an emerging country context. Third, we present empirically grounded practice implications for CSR.